2011
DOI: 10.1515/znc-2011-5-613
|View full text |Cite
|
Sign up to set email alerts
|

Purifi cation of a Toxic Metalloprotease Produced by the Pathogenic Photobacterium damselae subsp. piscicida Isolated from Cobia (Rachycentron canadum)

Abstract: The aim of the present study was to purify and characterize a toxic protease secreted by the pathogenic Photobacterium damselae subsp. piscicida strain CP1 originally isolated from diseased cobia (Rachycentron canadum). The toxin isolated by anion exchange chromatography, was a metalloprotease, inhibited by L-cysteine, ethylenediaminetetraacetic acid (EDTA), ethylene glycol-bis(β-aminoethyl ether)N,N,N’,N’-tetraacetic acid (EGTA), 1,10-phenanthroline, N-tosyl-L-phenylalanine-chloromethyl ketone (TPCK), and N-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Koo et al (2007) identifi ed PLA activity as an important factor in the cytotoxicity and lethality caused by Vibrio vulnificus. In the present study (Table IV), the purifi ed recombinant protein (LD 50 value between 2 and 4 μg protein/g fi sh) was found more virulent than the metalloprotease from the same strain (LD 50 6.8 μg protein/g fi sh) (Liu et al, 2011). As the LD 50 value of the recombinant protein was similar to that of the total ECP (LD 50 3.25 μg protein/g fi sh), it must be considered as an important virulence factor in ECP of the bacterium.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Koo et al (2007) identifi ed PLA activity as an important factor in the cytotoxicity and lethality caused by Vibrio vulnificus. In the present study (Table IV), the purifi ed recombinant protein (LD 50 value between 2 and 4 μg protein/g fi sh) was found more virulent than the metalloprotease from the same strain (LD 50 6.8 μg protein/g fi sh) (Liu et al, 2011). As the LD 50 value of the recombinant protein was similar to that of the total ECP (LD 50 3.25 μg protein/g fi sh), it must be considered as an important virulence factor in ECP of the bacterium.…”
Section: Discussionsupporting
confidence: 50%
“…In previous studies, phospholipase (PL) and protease activities were found in the extracellular products (ECP) of Phdp (Hu, 2005;Liu et al, 2011). The extracellular protease was purifi ed and characterized as a 34.3-kDa toxic metalloprotease (Liu et al, 2011), however, the extracellular PL required further characterization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations